2013
DOI: 10.1007/s00404-013-2738-7
|View full text |Cite
|
Sign up to set email alerts
|

Are there changes in characteristics and therapy of young patients with early-onset breast cancer in Germany over the last decade?

Abstract: Young breast cancer patients in Germany can still be regarded as a special group. Although tumors are now more often detected before reaching the lymph nodes than 10 years ago, an even bigger percentage is triple negative. Operative treatment has improved to a less aggressive way. Still operative and medical treatments have to be chosen after very careful evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Basal-like breast cancer is often approximated with the triple negative breast cancer subtype [7]. Triple negative breast cancer is characterized by an adverse prognosis particularly in case of limited sensitivity against neoadjuvant chemotherapy [5,16,24]. It is well described that molecular breast cancer subtypes are associated with significant differences in prognosis [28,35].…”
Section: Introductionmentioning
confidence: 99%
“…Basal-like breast cancer is often approximated with the triple negative breast cancer subtype [7]. Triple negative breast cancer is characterized by an adverse prognosis particularly in case of limited sensitivity against neoadjuvant chemotherapy [5,16,24]. It is well described that molecular breast cancer subtypes are associated with significant differences in prognosis [28,35].…”
Section: Introductionmentioning
confidence: 99%
“…This program is unique in that accompanying children were also offered psychological counseling. An earlier analysis showed that the young mothers with BC from this rehabilitation clinic can be regarded as a well-mixed collective with a high degree of representativeness for young BC patients in Germany [2]. However, the access criteria introduced a selection bias: At least 1 child up to the age of 12 and non-metastatic BC were mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…About every 10th woman diagnosed with BC in Germany is younger than 45 years [1] and may not yet have completed her family planning. Younger women are often affected by a more aggressive form of the disease [2], and BC is the most common cause of death in these women [1]. …”
Section: Introductionmentioning
confidence: 99%
“…Patients with large tumors, not well differentiated, with no expression of hormonal receptors are expected to have worse prognosis and were treated more aggressively. These tumors are particularly prevalent in young patients (women less than 35 years old) and in spite of many developments in this area, this group is still a special one [2]. The research mark in the past two decades was the discovery of HER2, which showed that patients' treatment must be supported by a molecular understanding of breast tumors.…”
Section: Introductionmentioning
confidence: 98%